Pathogenicity and virulence of Aspergillus fumigatus - Kayleigh Earle; Clara Valero; Daniel P. Conn; George Vere; Peter C. Cook; Michael J. Bromley; Paul Bowyer; Sara Gago (Virulence, 2023)
Pulmonary infections caused by the mould pathogen Aspergillus fumigatus are a major cause of morbidity and mortality globally. Compromised lung defences arising from immunosuppression, chronic respiratory conditions or more recently, concomitant viral or bacterial pulmonary infections are recognised risks factors for the development of pulmonary aspergillosis. In this review, we will summarise our current knowledge of the mechanistic basis of pulmonary aspergillosis with a focus on emerging at-risk populations.